Leadership barriers and the development in the perspective of dentists as heads of dental public health department in southern community hospitals - ป.ปาน เต็มสิริ; ตระกูลมุทุตา จุฑามณี; ยูรวงศ์ ณัฐพร (Thai Dental Public Health Journal, 2018)
The objectives of this analytical study were to study the leadership barriers and leadership development among 134 heads of dental department in southern community hospitals. The data was collected during November 2016 to February 2017 using self-administered questionnaire which consisted of personal data and the open-ended questions about the leadership barriers and development approaches in their perspectives. The quantitative data was analyzed using descriptive statistics, chi-square and Fisher’s exact test which significant level was set at 0.05. The qualitative data was carried out by classifying, grouping and content analysis by 2 researchers. The response rate was 76.9%. The barrier aspects were their traits and insufficient skill, factors related to their colleague, organization aspect, and others 74.8, 17.5, 9.7 and 3.9 percent, respectively. The highest educational level was significantly related to the barrier of traits and skill whereas professional positions and the number of years as the department head were significantly related to the organization aspect. Leadership development approaches were suggested such as self-developments (34.0 percent), taking a leadership training course (30.1 percent), sharing experiences among department heads or successful leaders (14.6 percent), and enhancement of leadership development in under-graduate curriculum (9.7 percent). The highest educational level was significantly related to the suggestion of enhancing leadership in undergraduate curriculum. Whereas professional positions and the number of years as the department head were significantly related to other aspect suggestion.